Riccia sarieae (Ricciaceae: Marchantiophyta)—a new species from a fragmented hillock of the Western Ghats, India - Daniels, A.e.d.; Daniels, D.t.t. (Phytotaxa, 2022)
Riccia sarieae, a new species of Riccia, is described from Marunthuvazhmalai, a fragmented hillock of the Southern Western Ghats. The distinctive features of the species are quadrate to rounded-quadrate epidermal cells, ovoid to roughly tetrahedral spores lacking an equatorial wing, crenulate, 9–11 areolae, with ridged areolations.